Labor incidents impact on tile cost structure in Colorificio Pordecar, C.A Company (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
This research was carried out in Colorificio Pordecar, C.A company, which is engaged in the manufacture and marketing of raw materials for the ceramic industry, decorative pieces and tiles for floors and walls. The study focused on the analysis of cost structure of major products such as tile, to assess the impact of labor incidents in total production costs, degree of importance which had not been considered for the purposes of estimating sales prices. To collect information, a questionnaire was applied to 40 employees and interviews to 4 people in the administrative area of the company. Direct observation was used. Data was quantified and tabulated to conclude that there are failures in regards to accounting. The unit cost increases considerably when including incidents as costs of labor, manifested in the Workers Collective Contract of the company under study, consequently if it is not considered, it might mean a real reduction in its profitability margin that threatens financially organization sustainability.
Keywords: labor incidents; costs of labor; cost structure